Pengaruh Pengungkapan Environmental, Social, and Governance terhadap Agresivitas Pajak dengan Manajemen Laba Sebagai Variabel Mediasi - Faradita, Mutia Putri; Kurniawan, Rahmat (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The study aims to test and demonstrate the impact of Environmental, Social, and Governance (ESG) disclosure on tax aggressiveness with profit management as a mediation. The research was carried out using the quantitative method involving 26 companies listed on the Indonesian Stock Exchange (BEI) from 2019 to 2021. Data collection methods used are library studies or documentation methods. The results of this study show that in part, ESG disclosure has no effect on tax aggressiveness, while ESG exposure has a negative effect on profit management, as well as profit management has a positive impact on tax agresiveness. The results in this study also show that with the analysis of the profit management pathway can mediate the impact of Environmental, Social, and Governance (ESG) disclosures on tax aggression. The research provides the constitution as a literature for further researchers and as additional information and input material for investors in making decisions. For governments, it can be an input to make more specific policies in the implementation of Environmental, Social, and Governance (ESG) and input in evaluating and maximizing tax-related policies.